Dampak Ekonomi Usaha Pengolahan Sagu (Metroxilon) di Desa Laloumera Kecamatan Besulutu Kabupaten Konawe - Sidarlis, Sidarlis; Salam, Idrus; Fyka, Samsul Alam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aims to determine the economic impact caused by sago processing business activities in the Village Laloumera Besulutu District Konawe. Determination of the sample is done by census consisting of 4 groups of sago processing farmers as much as 20 respondents so that obtained 20 respondent farmers as research sample. Data analysis used is descriptive analysis and multiplier analysis. The results of the study show that direct economic impact (Direct Impact) received by business unit owners per month amounted to Rp47,470,000, indirect impact (Indirect Impact) received by a local workforce of Rp8,488,000 and induced impact (Induced Impact) is a local manpower expenditure of Rp6,988,000. The value of Keynesian Income Multiplier is 0.83. Ratio Income Multiplier Type I equal to 1.18 and Ratio Income Multiplier Type II equal to 1.32. This shows that at this time sago processing business has an economic impact, although still considered quite small. This economic impact occurs because of the velocity of money between farmers, business units, and labor.